"Ellen Is Our Man": PERCEPTIONS OF GENDER IN POSTCONFLICT LIBERIAN POLITICS. Issue 1 (2nd January 2016) - Garnett, Tanya Ansahta
Abstract: This article examines the nature of shifting gender roles in Liberia's postconflict reconstruction process. Specifically, it investigates the ways in which political authority is gendered and the agency that women in politics employ to justify their participation as they attempt to reduce gender inequalities at the institutional level. I argue that the intervention of the international community has been instrumental in providing space and resources for gender mainstreaming, however in the absence of more in-depth intersectional analyses of gender dynamics, the unintended consequences of peacebuilding policies could hinder the sustainability of long-term peace. This article is based on a qualitative research country study conducted by the author in rural and urban Liberia following the election of Ellen Johnson Sirleaf. A discussion of key findings is exemplified with excerpts from key informant interviews and focus group discussions that seek to give voice to a cross-section of Liberians, so that they can contribute to the ongoing debate on gender mainstreaming in postconflict societies and bridge the gap between local and international discourses.